Human professional skills assessment based on a modified learning curve model - Angela Lago Alvarez; Wael M. Mohammed; Jose Luis Martinez Lastra (Production and Manufacturing Research: An Open Access Journal, 2025)
The rapid development of automation and digital technologies poses significant challenges and opportunities for the future of work. One of the key issues is keeping the Human-in-the-loop while enhancing workers´ professional skills to adapt to the dynamic demands of the labour market. Within this gap, this paper proposes a novel approach that integrates a modified version of Wright´s Learning Curve model and an upskilling model. The aim is to capture the skill learning progress by performing repetitive tasks and categorizing them into different skill levels. Finally, to demonstrate the approach, a case study of a manually executed workstation of a manufacturing process is introduced.